2008
DOI: 10.1007/s10433-008-0076-6
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational contact beyond the dyad: the role of the sibling network

Abstract: In this paper we aim to reach beyond the dyadic perspective on intergenerational contact and examine the influence of the sibling network on parent-child contact. We include aggregate sibling network characteristics as well as the adult child's position in the network vis-à-vis siblings, and use data from the Netherlands Kinship Panel Study (2002)(2003)(2004) NKPS; N = 4,601 dyads). Regarding aggregate network characteristics results show that having sisters, having stepsiblings, increasing geographical distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 34 publications
1
27
0
1
Order By: Relevance
“…Finch and Mason (1993) have described in detail how family responsibilities are negotiated over time, and how some children in the family end up committing themselves to taking care of parents, while others do not. Earlier research has demonstrated, perhaps contrary to common belief, that having fewer siblings increases the probability of providing help (Spitze and Logan 1991;Stuifbergen et al 2008;Brandt, Haberkern, and Szydlik 2009) and keeping in touch with parents (van Gaalen, Dykstra, and Flap 2008). Having many siblings may make it easier to avoid care responsibility by passing it on to brothers, and in particular to sisters.…”
Section: More Children -More Care?mentioning
confidence: 90%
“…Finch and Mason (1993) have described in detail how family responsibilities are negotiated over time, and how some children in the family end up committing themselves to taking care of parents, while others do not. Earlier research has demonstrated, perhaps contrary to common belief, that having fewer siblings increases the probability of providing help (Spitze and Logan 1991;Stuifbergen et al 2008;Brandt, Haberkern, and Szydlik 2009) and keeping in touch with parents (van Gaalen, Dykstra, and Flap 2008). Having many siblings may make it easier to avoid care responsibility by passing it on to brothers, and in particular to sisters.…”
Section: More Children -More Care?mentioning
confidence: 90%
“…Recent studies have highlighted the importance of examining intergenerational exchanges within the larger family context (Bengtson, 2001;Cong & Silverstein, 2011a;Davey et al, 2004;Eggebeen, 1992;Leopold & Raab, 2013;Tolkacheva et al, 2010;Van Gaalen et al, 2008). They have called for an examination of within-family differences and variations in parents' giving among children, i.e., the exchange between the parents and each child in a family rather than the children as an aggregate (Silverstein & Giarrusso, 2010;Suitor, Pillemer, & Sechrist, 2006).…”
Section: The Network Family Approachmentioning
confidence: 97%
“…The literature on parent-toadult child relations and grandparenting has long examined parental caregiving as an instrumental or practical component of intergenerational transfers or exchange (Soldo & Hill, 1993). The latest development in intergenerational transfer studies moves beyond the parent-child dyad to examine the issue from the extended family network perspective (Cong & Silverstein, 2011a;Davey, Janke, & Savla, 2004;Eggebeen, 1992;Leopold & Raab, 2013;Tolkacheva, van Groenou, & van Tilburg, 2010;Van Gaalen, Dykstra, & Flap, 2008), paying attention to the lineage factor by considering daughters and in-laws as providers of elder care and family support (Cong & Silverstein, 2008a, 2008bWillson, Shuey, & Elder, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Ouders die hulpbehoevend worden, kunnen de meeste praktische steun verwachten van de kinderen die het dichtstbij wonen. Natuurlijk speelt ook een rol dat volwassen kinderen die dicht bij hun ouders wonen meer contact met hen hebben (Van Gaalen, Dykstra & Flap, 2008), waardoor ouders en kinderen beter op de hoogte zijn van elkaars noden. Beide redeneringen brengen ons tot de hypothese dat kinderen die dicht bij hun ouders wonen, een grotere kans hebben op het ontvangen van financiële steun dan kinderen die verder weg wonen.…”
Section: Verwachte Reciprociteitunclassified